Body Carrier’s- The Core of Illicit Trafficking (International Journal of Innovative Research in Computer Science & Technology, 2022)
When ingested, a drug is a harmful  chemical that alters the physiology or psychology of  creatures. Inhalation, injection, smoking, and dissolution  beneath the tongue are all methods of drug ingestion.  Drugs are derived from medicinal plants as well as organic  synthesis. Several criminals operate under the guise of  being drug dealers. "Internal carries, internal carries,  internal carries, internal carries, internal Mule, body  packer, and mule. Drug smuggling utilizing the human  body as a conveyance is known as body packing. Cocaine  and heroin are often wrapped in waterproof material. Latex  or condoms, for example. People may see illicit drug use  in the shape of body packers everywhere around us.  Storing heroin and morphine in the form of gender pellets  for an extended period might result in death. Penalties are  determined by the Narcotic Psychotropic Substances Act  of 1985. During a first conviction, the suspect faces a  punishment of Rs 1-2 lakh and a minimum of 10 years in  jail. If convicted again, a fine of 3-5 lakh rupees will be  imposed, as well as a sentence of at least 20-30 years in  jail. In this paper author talks about Body Carriers are at  the heart of illegal trafficking. It is also found that package  aspects such as color, packing materials, wrapper design,  or innovations are more crucial considerations to consider  when a buyer makes a purchasing choice. Finally, it was  discovered that one of the most essential and strong factors  influencing customer purchasing decisions is packing.
Keywords: Body pusher; Internal carries; Inhalation; Mule; Smuggling